2021
DOI: 10.3386/w29587
|View full text |Cite
|
Sign up to set email alerts
|

Taking the Pulse of Nations: a Biometric Measure of Well-being

Abstract: A growing literature identifies associations between subjective and biometric indicators of wellbeing. These associations, together with the ability of subjective wellbeing (SWB) metrics to predict health and behavioral outcomes, have spawned increasing interest in SWB as an important concept in its own right. However, some social scientists continue to question the usefulness of SWB metrics. We contribute to this literature in three ways. First, we introduce a biometric measure of wellbeing -pulse -which has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Blanchflower and Oswald (2016) found that men were also less likely to take anti-depressant medications. Using data from the Health Survey for England for the period 1998-2018, Blanchflower and Bryson (2021a) found that men had significantly lower pulse rates than women as well as lower GHQ scores, were less anxious and had better general health. This was true with and without controls for marital status and income.…”
Section: Q1 "When Things Go Wrong In My Life It Takes a Long Time To ...mentioning
confidence: 99%
“…Blanchflower and Oswald (2016) found that men were also less likely to take anti-depressant medications. Using data from the Health Survey for England for the period 1998-2018, Blanchflower and Bryson (2021a) found that men had significantly lower pulse rates than women as well as lower GHQ scores, were less anxious and had better general health. This was true with and without controls for marital status and income.…”
Section: Q1 "When Things Go Wrong In My Life It Takes a Long Time To ...mentioning
confidence: 99%
“…In Blanchflower and Bryson (2023b) we estimated US state and country rankings of negative and positive affect using the Gallup World Poll (GWP) and the US Daily Tracker for the period 2010 through 2017. There were no data available from the US Daily Tracker in other years, but the Gallup World Poll has data on several positive affect variables that we examined -Cantril's 11step life satisfaction variable question Q1 above, plus three other binary variablesenjoyment, smiling and being well-rested plus four binary negative affect variablesworry, sadness, anger and pain.…”
Section: 5: Gallup World Poll Data For Europe 2005-2023mentioning
confidence: 99%